Signaling Effects on the Labor Market: Winners and Losers of University Licensing in a Higher Education Reform - Pablo Lavado; Gustavo Yamada; Joaquin Armas; Mauricio Gonzalez (Institute of Labor Economics (IZA), 2024)
We investigate the effects of a higher education reform on the labor market outcomes of college graduates in Peru. The cornerstone of this piece of legislation was a licensing process whereby a newly created higher education superintendency evaluated every existing university on minimum quality criteria to grant or deny their operating license. We find that, conditionally on being employed, the effects of this reform on the college graduates of universities that were granted (denied) the license were two: an effect of around 6.5% (-9%) on monthly wages and a less precisely estimated effect of approximately 4 p.p. (-3.5 p.p.) on the probability of being formally employed. Our work provides evidence of the existence of winners and losers as a consequence of this ambitious higher education reform in Peru.
Keywords: I26; I28; J01; L14; 330; SUNEDU; university licensing; higher education reform; signaling effects